1989
DOI: 10.1159/000163519
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Lewis Antigenic Determinants in Colorectal Adenocarcinomas

Abstract: Expression of type 1 and type 2 chain Lewis antigens was studied in 32 rectal adenocarcinoma specimens; the results were correlated with the patients’ Lewis phenotype and secretor status. In addition, the pattern of expression of these antigens was analyzed in adjacent and distant normal mucosa. We used an indirect immunofluorescence technique with p-phenylenediamine counterstaining (Oriol technique) and a panel of monoclonal antibodies directed against the different antigenic specificities. Normal distal colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Several authors have found no significant differences in the expression of Le y in CRC tumour tissue in comparison with healthy mucosa (40). However, our reported change in Le y expression is consistent with those of previous studies (27,28,41,42) which have justified the classical consideration of this determinant as an oncofetal antigen (43) and a premalignant biomarker of distal CRC (18,40). In this regard, it should be noted that tumour biomarkers are not only monitors for diagnosis or monitoring of patients, but represent real characteristics of cancer cells.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Several authors have found no significant differences in the expression of Le y in CRC tumour tissue in comparison with healthy mucosa (40). However, our reported change in Le y expression is consistent with those of previous studies (27,28,41,42) which have justified the classical consideration of this determinant as an oncofetal antigen (43) and a premalignant biomarker of distal CRC (18,40). In this regard, it should be noted that tumour biomarkers are not only monitors for diagnosis or monitoring of patients, but represent real characteristics of cancer cells.…”
Section: Discussionsupporting
confidence: 93%
“…3), in spite of previous evidence showing a correlation between the increased expression of Le b and the Dukes' stage of each specimen (19,26). On the contrary, other studies have reported the uniform Le a distribution throughout the colon before and after the occurrence of CRC (27,28), or even its reduced expression in parallel with the appearance of colorectal malignancy (16,20). In any case, our apparent increase of a(1,2)FT activity in the tumour colonic tissue is in line with histological (29) and a(1,2)FT cDNA-transfected rat colon cell lines (30) studies, and with them we suggest that since this key enzyme acts on core 1, it could be responsible for regulating the expression of both Le a and Le b antigens, in competition with the a (1,4) FT for this common acceptor (29).…”
Section: Discussionmentioning
confidence: 82%
“…57-S9, 62-64). Conversely, as compared to the normal corresponding tissues, it decreases in colon prostate and breast carcinomas (30,34,72,73). In the case of the Leb antigen, the situation is rather similar to that of the A and B antigens.…”
Section: The Leicis Untigensmentioning
confidence: 98%
“…In the case of the Leb antigen, the situation is rather similar to that of the A and B antigens. Its level of expression is increased in carcinomas from the distal colon, the rectum, the thyroid and the liver (28,45,47,54,(72)(73)(74)(75), but also from the urinary bladder, while it decreases in stomach carcinomas (59,62,64). Finally, the Ley antigen has its expression strongly augmented in nearly all types of carcinomas (17, 28, 35, 40, 41, 4 3 4 5 , 48, 72, 73, [76][77][78][79][80][81] with the exception of the pancreatic and possibly endometrial carcinomas for which a decrease has been reported (58,70,7 1,82).…”
Section: The Leicis Untigensmentioning
confidence: 99%
“…Blood group-related antigens (BGA) are oligosaccarides widely distributed in the body, especially in epithelial cells (1)(2)(3)(4)(5)(6). In most individuals (approximately 80%), they are also found in secretions (saliva, gastric juice); these individuals are denominated "secretors".…”
mentioning
confidence: 99%